2010
DOI: 10.1093/nar/gkq1077
|View full text |Cite
|
Sign up to set email alerts
|

ZFIN: enhancements and updates to the zebrafish model organism database

Abstract: ZFIN, the Zebrafish Model Organism Database, http://zfin.org, serves as the central repository and web-based resource for zebrafish genetic, genomic, phenotypic and developmental data. ZFIN manually curates comprehensive data for zebrafish genes, phenotypes, genotypes, gene expression, antibodies, anatomical structures and publications. A wide-ranging collection of web-based search forms and tools facilitates access to integrated views of these data promoting analysis and scientific discovery. Data represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
224
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(224 citation statements)
references
References 8 publications
0
224
0
Order By: Relevance
“…S4) and the rpl7l1 mutant apparently has a mild phenotype (source: ZIRC). By contrast, its paralogue rpl7 has been demonstrated to be strongly and ubiquitously expressed (Bradford et al, 2011). A similar situation might occur in Drosophila, where RpL7 has been shown to be specifically required in neuroblasts to maintain their proliferation (Neumüller et al, 2011), whereas its counterpart (RpL7-like) displays ubiquitous expression.…”
Section: The Expression Of Genes Coding For Ribosomal Protein Is Crucmentioning
confidence: 85%
“…S4) and the rpl7l1 mutant apparently has a mild phenotype (source: ZIRC). By contrast, its paralogue rpl7 has been demonstrated to be strongly and ubiquitously expressed (Bradford et al, 2011). A similar situation might occur in Drosophila, where RpL7 has been shown to be specifically required in neuroblasts to maintain their proliferation (Neumüller et al, 2011), whereas its counterpart (RpL7-like) displays ubiquitous expression.…”
Section: The Expression Of Genes Coding For Ribosomal Protein Is Crucmentioning
confidence: 85%
“…To identify the molecular events underlying the synthesis of oxytocin, we screened the zebrafish model organism database (ZFIN) (Bradford et al, 2011) for transcriptional regulators expressed in the neurosecretory preoptic area (NPO), which includes neurons expressing the zebrafish homolog of oxytocin, termed oxytocin-like (Oxtl) (Blechman et al, 2007). One such candidate was the gene encoding the zebrafish ortholog of the transcriptional coactivator PGC-1␣ (LeMoine et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The close phylogenetic relationship between goldfish and zebrafish (Saitoh et al, 2003, 2006) suggest that the well‐established molecular techniques, as well as mutant, morphant, and gene expression patterns, catalogued in The Zebrafish Model Organism Database (Bradford et al, 2011), can be directly applied to goldfish research (Mabee et al, 2007; Schlling and Webb, 2007; Tsai et al, 2013). Moreover, it was recently confirmed that these two teleost species are similar in terms of embryological development (Tsai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%